1970
DOI: 10.1136/bmj.1.5695.526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paracervical Nerve Block Anaesthesia during Labour

Abstract: provide the sole means of analgesia throughout the first stage of labour.Only 48% of the primigravidae required no other form of analgesia, as against 72% of the multiparae.Complications included a 17% incidence of maternal haemorrhage during insertion of the continuous needle, an overall fetal bradycardia rate of 11%, and two perinatal deaths foliowing single paracervical block. It is concluded that the use of continuous paracervical block should be discontinued, and that amide-type local anaesthetic agents s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As with lidocaine and mepivacaine, paracervical nerve block anaesthe sia during labour resulted in significant rates of fetal bradycardia [Murphy et al, 1970] as well as increased maternal and fetal blood levels in some cases [Hollmén et al, 1969]. It has been concluded that, because of such adverse effects, the amide-type local anaesthetic drugs should not be used for single paracervical block (see Lidocaine and Mepivacaine).…”
Section: Transfer To the Fetus At Termmentioning
confidence: 99%
“…As with lidocaine and mepivacaine, paracervical nerve block anaesthe sia during labour resulted in significant rates of fetal bradycardia [Murphy et al, 1970] as well as increased maternal and fetal blood levels in some cases [Hollmén et al, 1969]. It has been concluded that, because of such adverse effects, the amide-type local anaesthetic drugs should not be used for single paracervical block (see Lidocaine and Mepivacaine).…”
Section: Transfer To the Fetus At Termmentioning
confidence: 99%